The methodology of sharpening of blade tools made of superhard materials - Fedorovich, V.; Ostroverkh, Y.; Kozakova, N. (Національний технічний університет "Харківський політехнічний інститут", 2019)
High durability of the blade tool from superhard materials (SНM), which have unique physical and mechanical properties, creates the prerequisites for its effective use in automated production. However, the widespread use of such tools is constrained by its relatively low reliability during operation. This disadvantage is due to the imperfection of the processes of obtaining SНM: the presence in it residual stresses, internal defects, which appear even after sharpening and thermo-activated finishing. The processes of sharpening of tool blade from superhard materials and cutting with this tool are characterized by high levels of contact pressures and temperatures in the treatment area. Therefore, it seems inappropriate to choose sparing conditions for its sharpening and refinement to ensure the defect of these processes. In connection with this, a new methodological approach is proposed, which makes it possible to determine the cutting conditions and other conditions for sharpening and finishing the SНM blade tool, in which material defects are revealed even at the tool manufacturing stage. To this end, in the software packages COSMOS, ANSYS, NOSTRAN, Third Wave AdvantEdge, thermo-force stress in the cutting edge of the tool simulated under extreme conditions while its operation. This simulations are the initial data for solving the inverse problem – finding conditions (speed, cross feed, normal pressure in the contact) and other diamond grinding modes (physical and mechanical properties of the bond and diamond grains of the wheel, grain size and concentration) according to the well-known stress-strain state cutter from SНM in extreme conditions of its operation. The proposed methodology allows rejecting defective cutters at the stage of their manufacture, thereby increasing the reliability of operation of blade tool from superhard materials.

Висока стійкість лезового інструмента з надтвердих матеріалів (НТМ), яким притаманні унікальні фізико-механічні властивості, створює передумови для його ефективного застосування в автоматизованому виробництві. Однак, широкое застосування такого інструмента стримується відносно невеликою надійністю його при експлуатації. Цей недолік зумовлено недосконалістю процесів виробництва НТМ: наявністю у них залишкових напруг, внутрішніх дефектів, які виявляються навіть після заточування й термоактивованого доведння. Процес заточування лезового інструмента з надтвердих матеіалів і різання цим інструментом характеризуються високими рівнями контактних тисків і температур у зоні обробоки. Тому видається некоректним вибір щадних умов його заточування й доведення для забезпеченин бездефектності даних процесів. У зв’язку із цим пропонується новий методологічний підхід, який дозволяє визначати режими й інші умови заточування і доведення інструмента з НТМ, за яких дефекти матеріала розкриваються ще на стадії виготовлення інструмента. З тією ж метою в пакетах прикладних програм COSMOS, ANSYS, NOSTRAN, Third Wave AdvantEdge моделюються термосилові напруги у ріжучому клині різця, що виникають в екстремальних умовах його експлуатації. Вони ж є вихідними даними для розв’язання зворотньої задачі – знаходження режимів (швидкості, подачі, нормального тиску в контакті) й інших умов алмазного шліфування (фізико-механічних властивостей зв’язування й алмазних зерен круга, їхньої зернистості й концентрациії) за відомим напружено-деформованим станом різця з НТМ в екстремальних умовах його експлуатації. Запропонована методологія дозволяє відбраковувати дефектні різці ще на стадії їх виготовлення, тим самим, підвищувати надійність експлуатації лезового інструмента з надтвердих матеріалів
Методологія заточування лезового інструмента з надтвердих матеріалів
Keywords: extreme operating conditions; stress-strain state; diamond grain; grinding conditions; екстремальні умови експлуатації; алмазне зерно; режими шліфування; напружено-деформований стан